Working into the B Language: The Condoned Taboo? - Lim, Hyang-Ok (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractA survey was conducted in 2003 among Korean-English interpreters residing in Korea to study their views regarding interpreting into B — something that is considered the norm in some countries, while almost taboo in other countries. Following the first survey, a second similar survey was conducted among AIIC members across the world. This compares the two surveys in an attempt to determine whether the sentiment about interpreting into B is different among interpreters — regardless of their language combination — or whether it is relatively the same.